Prophecy and Religion Revisited: John Skinner and Evangelical Biblical Criticism - Houston, Walter (Religions, 2021)
The paper is an essay in the history of interpretation. Its subject is John Skinner’s book on the life of Jeremiah, Prophecy and Religion (1922). The main aim is to place the work in its historical, theological and cultural context, to explain Skinner’s conviction that Jeremiah’s life marks the emergence of personal religion in Israel and points towards Christianity. Attempts at such contextualization by J. Henderson and M.C. Callaway are studied and shown to be inadequate. Skinner’s religious context and theological education are then reviewed and are shown to be sufficient to account for his belief in the pivotal role of Jeremiah in the evolution of ‘religion’. The paper finally addresses the present-day significance of Skinner’s work and concludes that while Prophecy and Religion is of limited value for the interpretation of Jeremiah, Skinner’s life and work as a whole as an evangelical believer engaged in radical biblical criticism is a valuable model neglected over the last 100 years.